Strategy and mechanism of One Health governance: case study of China - Xinchen Li; Yanyan Zhang; Qiyu Zhang; Jingshu Liu; Zelin Zhu; Xinyu Feng; Lefei Han; Xiaoxi Zhang (Science in One Health)
Background: Strategy and mechanism are crucial components of One Health governance in China, designed to address the interconnected health issues between humans, animals, and the environment. This study aims to evaluate China's current One Health governance framework, identify key strengths and gaps, and provide recommendations for establishing a more integrated and effective system. Methods: A qualitative approach was employed, including in-depth interviews, policy analysis, and a review of existing literature, to evaluate the strengths and gaps in China's One Health framework. Results: The analysis identified progress and challenges in six key areas: (1) political commitment: strong national support exists, but lacks a unified strategy; (2) legislation and regulation: notable legislative efforts are in place, yet they remain fragmented; (3) leadership building: effective leadership structures have been established during crises but are not institutionalized; (4) strategic planning: initial regional planning is underway, but a comprehensive national focus is needed; (5) coordination and communication: mechanisms exist but require formalized, consistent information-sharing channels; (6) stakeholder engagement: public and academic awareness is growing, yet local community involvement needs strengthening. Conclusion: To advance its One Health governance, China must focus on creating a unified strategy, enhancing interdepartmental coordination, and deepening stakeholder engagement, ensuring its alignment with international standards and improving public health outcomes.